Le jardin comme post-paysage et projection imaginée - Jean-Simon DesRochers (Projets de Paysage)
The garden presents a version of reality under control, a determined variable of landscape. As Berque mentions, landscape, as a concept, does not exist outside of the mind. With the idea of proto-landscape, he suggests a transcultural common denominator of environement appreciation in cultures where the concept of landscape is absent. At the other end of the spectrum, the garden would present the characteristics of a post-landscape, the imagined determination of a subjective perception that we aspire to objectivise. Following the neurobiological observation of Damasio, it would be adequate to affirm that the garden offer to experiment emotionally the sentiment of an imagined place. The analysis of post-landscape allow us to precise the relationship of humans with their perception of the environment and the interactions they wish to promote, but mostly, it presents a portrait of the relation between humans and the perception of their own conscience.